Nonsense, política e HQ: os trunfos de Quando parei de me preocupar com canalhas (Tiago Vieira, 2015) - Lusvarghi, Luiza (Imagofagia, 2021)
Nonsense, política e HQ: os trunfos de Quando parei de me preocupar com canalhas (Tiago Vieira, 2015)